Peran Mindfulness dan Regulasi Emosi dalam Meningkatkan Psychological Well-being pada Guru TK di Surabaya - Zaulino, Naufal Herari; Nainggolan, Eben Ezer; Ul Haque, Sayidah Aulia (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2025)
Abstrack This study aims to examine the relationship between mindfulness and emotion regulation on psychological well-being among kindergarten teachers in Surabaya. The study population consists of 357 kindergarten teachers in Surabaya, selected using a purposive sampling technique. The research employed a descriptive quantitative method with a correlational approach. The research instruments include the Five Facet Mindfulness Questionnaire (FFMQ) with 24 items, the Emotion Regulation Questionnaire (ERQ) with 10 items, and the Psychological Well-Being Scales with 18 items, all of which were tested for validity and reliability. Data analysis was conducted using ordinal linear regression to evaluate the influence of mindfulness and emotion regulation on psychological well-being. The results indicate that mindfulness has a significant but negative influence on psychological well-being (p < 0.05), while emotion regulation does not show a significant influence (p > 0.05). These findings provide valuable insights for developing more targeted interventions to enhance the psychological well-being of kindergarten teachers. Keywords: Mindfulness, emotion regulation, psychological well-being. Abstrak Penelitian ini bertujuan untuk mengkaji hubungan antara mindfulness dan regulasi emosi terhadap psychological well-being pada guru TK di Surabaya. Populasi penelitian terdiri dari 357 guru TK di Surabaya yang dipilih menggunakan teknik purposive sampling. Metode penelitian yang digunakan adalah kuantitatif deskriptif dengan pendekatan korelasional. Instrumen penelitian mencakup five facet mindfulness questionnaire (FFMQ) dengan 24 item, emotion regulation questionnaire (ERQ) dengan 10 item, dan -psychological well-Being scales dengan 18 item, yang telah diuji validitas dan reliabilitasnya. Analisis data dilakukan dengan uji regresi linear ordinal untuk mengevaluasi pengaruh mindfulness dan regulasi emosi terhadap psychological well-being. Hasil analisis menunjukkan bahwa mindfulness memiliki pengaruh signifikan namun negatif terhadap psychological well-being (p < 0,05), sedangkan regulasi emosi tidak menunjukkan pengaruh yang signifikan (p > 0,05). Temuan ini memberikan wawasan penting bagi upaya pengembangan intervensi yang lebih terarah dalam meningkatkan Psychological Well-Being guru TK. Kata Kunci : Mindfulness, regulasi emosi, psychological well-being.